Degradation of polycyclic aromatic hydrocarbons (PAHs) and dibenzofuran by actinomyces strain XKDN12 - Nhã Nguyễn Đương; Minh Nghiêm Ngọc; Bảo Nguyễn Ngọc; Hà Đặng Thị Cẩm (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 123-132, 2005